Avaliação do comportamento de BTEX e seus metabólitos de biodegradação em solos: estudos de remedição em microcosmos - Niño Camacho, Leidy Rocío (2015)
The monoaromatic hydrocarbons composed by benzene, toluene, ethylbenzene and xylenes isomers (BTEX), are commonly found near local oil refineries, filling stations, or around pipelines, as a result ofleaks and/or spills. In such places, a microbial activity not only promotes the transformation of these compounds into products such as CO2 or methane, but also convert them into highly toxic and/or carcinogenic compounds. Some of the metabolites resulting from biotransformation process are benzylsuccinic acid, 2-methylbenzylsuccinic acid, isomers of toluic acid and benzoic acid. The aim of this study is to increase knowledge about the biodegradation of monoaromatic hydrocarbons in soils, by investigating their removal under three different conditions, and to evaluate the formation products associated with their degradation. This work was carried out with series of anaerobic microcosms with three different electron acceptors acting as oxidants: sulfate, nitrate and iron (III). The individual effect of each in a soil contaminated with BTEX and another set containing a mixture of these electron acceptors with soil contaminated with conventional diesel were investigated. The concentrations of BTEX and metabolites were monitored for 90 days. Previously, it was necessary to develop suitable analytical methods for monitoring BTEX through gas chromatography coupled with flame ionization detection (GC/FID) while high-performance liquid chromatography coupled to a mass spectrometer (LC-MS/MS) was used for determining the metabolites. A preliminary microbiological characterization of groups of bacteria was carried out, showing a prevalence of nitrate-reducing bacteria in the soil utilized. Evidence that the BTEX compounds may be removed in anaerobic conditions linked to nitrate and sulfate reduction were found. Using iron (III) like electron receptor was not observed a significant decrease in the concentration of contaminants during the three months of incubation, except for toluene. Results also show that toluene was the compound quite easily degraded in anaerobic conditions in soil, enriched with different electron acceptors. On the other hand the appearance of metabolites was quickly detected in the series of experiments employing nitrate, due to the higher content of native nitrate reducing bacteria in the soil, associated with the fact that nitrate has a higher oxidizing power from the electron receptors studied. In case of iron (III), metabolites were slow to appear, however higher concentrations were detected mainly of benzylsuccinic acid from toluene degradation. To establish a scenario more realistic of contamination, a soil was artificially contaminated with diesel. However, due to the large number of compounds present in the fuel, the toxicity of the medium was increased, causing inhibition of the biological activity and thus affecting the efficiency of BTEX removal.